Elements of Good Faith in Trademark Registration Under Indonesian Law: (Case Study of Supreme Court Decision No. 781 K/Pdt.Sus-HKI/2022) - Diana Putri Zalukhu (Locus Journal of Academic Literature Review, 2023)
The purpose of this study is to determine and analyze the legal certainty of the element of good faith as the protection of the implementation of trademark registration in Indonesia, the legal implications of the registration of a trademark that is canceled because it does not meet the elements of good faith in Indonesia; and legal considerations of judges in deciding cases in the Supreme Court decision number 781 K/PDT.SUS-HKI/2022 in providing legal certainty for trademark owners who register their trademarks in good faith. This type of research is normative research and descriptive analysis. This research uses library data collection techniques and is done by collecting and reviewing secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. The data collected is then analyzed with qualitative methods. The results of the study concluded that the strength of the element of good faith as the protection of the implementation of trademark registration in Indonesia can be said to still not be able to provide protection and legal certainty mascimal. The legal implications of the registration of a trademark that is canceled because it does not meet the elements of good faith in Indonesia is the cancellation and removal of trademarks by the Minister. Legal considerations of judges in deciding the case in the Supreme Court decision number 781K/Pdt.Sus-HKI/2022 in providing legal certainty for trademark owners who register their trademarks in good faith is wrong. The panel of judges should not use Article 21 paragraph (1) items b and c, but rather use Article 21 paragraph (3) of Law Number 20 Year 2016 as the basis for legal considerations in deciding the case.